LONG-DISTANCE TRUCK DRIVERS COPING STRATEGIES AND HARDINESS: SELF-ASSESSMENT PROCEDURE AND IMPLICIT ASSOCIATION TEST - Plotka, Irina; Igonin, Dmitry; Shaplavska, Jelena; Kruzite, Daiga; Blumenau, Nina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The activity efficiency of long-distance truck drivers is determined not only by professional knowledge and skills, but also the psychological features, such as hardiness and coping strategies to cope with stress. The relationship between coping strategies and hardiness measured with implicit methods has not been studied enough. The research aim is to study the relationship of hardiness measured by the Implicit Association Test (IAT) and self-assessment procedures with coping strategies among long-distance truck drivers. Research questions focused on the study of this relationship. Participants: 40 males, long-distance truck drivers, M=29.6, SD=6.9 years. Implicit method: Four experimental procedures of the IAT on the basis of two-categories were developed (IAT1 - Commitment, IAT2 - Control, IAT3 - Challenge, IAT4 - Hardiness). Explicit methods: "Dispositional Resilience Scale, DRS-15" (Bartone), Strategic Approach to the Coping Scale (Hobfoll). Positive and negative implicit effects for assessments of Hardiness, Control and Challenge were revealed. The greatest number of negative effects found in Challenge. The regression equation for the dependent variable Hardiness (implicit) contains predictors Control and Commitment, measured by the IAT. There is a difference in the relationship between coping strategies and implicitly and explicitly measured hardiness and its components.